Simulation research on the influence of special ships on waterway through capacity for a complex waterway system: a case study for the Port of Meizhou Bay. (April 2020) - Shang, Jianping; Wang, Wenyuan; Peng, Yun; Tian, Qi; Tang, Ying; Guo, Zijian
The study of waterway through capacity for ports is a challenging problem due to the randomness and complexity of the waterway system, which needs to be analyzed by simulation technology. This paper quantitatively studies the influence of special ships on waterway through capacity and provides corresponding measures to improve waterway through capacity. The complex waterway system in the Port of Meizhou Bay is employed as a case study. Considering the actual conditions in the Port of Meizhou Bay, including the ships, berths, waterways, and natural conditions, a Simio-based simulation model is established. The real operation data from the Port of Meizhou Bay in 2015 are used to verify the correctness and effectiveness of the model. The simulation results show that special ships reduce the waterway through capacity by 4.9% and suggest that circumnavigation strategies that can be adopted after the extension and new construction of waterway systems can improve the waterway through capacity by 5.9%.